A DESCRIPTIVE STUDY ON JOB SATISFACTION DRIVERS AMONG GENERATION Z EMPLOYEES - Davina Veronica; Verena Aurelia; Jocelyn Samantha; Lydia Stevani; Ismoro Reza Prima; Zamralita (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
In this modern era, the workforce is increasingly dominated by Generation Z (Gen Z), who tend to be flexible and open to technology. This study aims to analyze in greater depth the job satisfaction level of Gen Z as well as the factors that influence it. The research method used is descriptive quantitative, intended to describe the general job satisfaction of Gen Z through an online questionnaire distributed to Gen Z aged 20–28 years, who have worked for at least one year, and are either contract or permanent employees. The sampling technique used was convenience sampling, resulting in 106 respondents meeting the criteria. The results of the study show that the dimensions with the highest average scores (means) include supervision, coworkers, and the nature of work. This study concludes that the job satisfaction level of Generation Z employees generally falls within the moderate to high category.